Penerapan Metode PIECES Framework Pada Website Simkatmawa Sebagai Evaluasi Kepuasan Pengguna - Alviandri Umbu Kora; Suharyadi Suharyadi (STMIK Banjarbaru, 2025)
The Student Performance and Governance Information System (SIMKATMAWA) is a multi-user service website that functions in the field of student affairs and activities at national and international levels. The SIMKATMAWA website plays a role in presenting data related to student achievement to the Higher Education Institution (DIKTI) in the context of higher education transformation. The existence of this site is an effort to facilitate access to information about university activities, although users still face several obstacles in the process of using it. Therefore, the purpose of this study is to measure the level of satisfaction of users or authorized officers from the university in accessing the SIMKATMAWA site, by applying the PIECES Framework method (Performance, Information, Economy, Control, Efficiency, and Service). Data collection is done through questionnaires, literature studies, and data management analysis using a Likert scale. The results showed that by using the PIECES method, the SIMKATMAWA site proved to be very useful and played an important role in providing detailed information for university rankings.Keywords: Website of SIMKATMAWA; PIECES Framework; Ranking; Student Services AbstrakSistem Informasi Kinerja dan Tata Kelola Mahasiswa (SIMKATMAWA) adalah sebuah situs web layanan multi-pengguna yang berfungsi dalam bidang urusan mahasiswa dan kegiatan di tingkat nasional maupun internasional. Situs web SIMKATMAWA berperan dalam menyajikan data terkait prestasi mahasiswa kepada Lembaga Pendidikan Tinggi (DIKTI) dalam konteks transformasi pendidikan tinggi. Keberadaan situs ini merupakan upaya untuk memudahkan akses informasi mengenai aktivitas universitas, meskipun pengguna masih menghadapi beberapa kendala dalam proses penggunaannya. Oleh karena itu, tujuan penelitian ini adalah untuk mengukur tingkat kepuasan pengguna atau petugas yang berwenang dari universitas dalam mengakses situs SIMKATMAWA, dengan menerapkan metode Kerangka PIECES (Kinerja, Informasi, Ekonomi, Kontrol, Efisiensi, dan Layanan). Pengumpulan data dilakukan melalui kuesioner, studi literatur, dan analisis manajemen data menggunakan skala Likert. Hasil penelitian menunjukkan bahwa dengan menggunakan metode PIECES, situs SIMKATMAWA terbukti sangat berguna dan berperan penting dalam menyediakan informasi yang mendetail untuk perankingan universitas.Kata Kunci: Website SIMKATMAWA; PIECES Framework; Pemeringkatan; Layanan Kemahasiswaan